Crime and Nourishment: A Narrative Review Examining Ultra-Processed Foods, Brain, and Behavior - Susan L. Prescott; Alan C. Logan; Erica M. LaFata; Ashka Naik; David H. Nelson; Matthew B. Robinson; Leslie Soble (Dietetics)
Recently, there has been increased scientific and clinical interest in the potential harms associated with ultra-processed foods, including poor mental health, aggression, and antisocial behavior. Research spanning epidemiology, mechanistic pre-clinical work, addiction science, microbiome and exposome science, and human intervention trials has underscored that nutrition is of relevance along the criminal justice continuum. As such, the emerging dietetics research is salient to the thousands of international psychologists and allied mental health professionals that are engaged in justice work, including forensics, prevention, and intervention. In addition, relationships between nutrition and behavior relate to “food crime”, an emergent area unifying criminal justice researchers with psychology, public health, and other interdisciplinary sectors. Food crime scrutinizes the vast harms, including non-communicable diseases and adverse behavioral outcomes, as influenced by the distribution of addictive ultra-processed food products. Here, we examine the emergent research, including biophysiological mechanisms, and evidence indicating that dietary patterns/components intersect with psychosocial vulnerabilities linked with risks of antisocial behavior and justice involvement. Viewed through a prevention lens, the study of nutrition and aggressive behavior should be prioritized, especially if the outcomes emerge as externalities of the global consumption of ultra-processed food. In the context of criminal justice and behavior, there is a need for forensic examination of how industry influence and power structures can undermine matters of food justice.